Strategi Pengembangan Vaksin Dengue - -, Paisal; -, Subangkit (Jurnal Biotek Medisiana Indonesia, 2013)
Dengue fever is a disease endemic in Indonesia. The disease is caused by dengue virus serotypes DENV1, DENV2, DENV3, and DENV4. One way to control the disease is dengue vaccine discovery. This review based on the study of literatures that showed currently several strategies for dengue vaccine development are live attenuated vaccine, subunit vaccines, and DNA vaccines. Dengue vaccine development still face challenges, especially the formulation of vaccines that can trigger an immune response against all four serotypes and the absence of a suitable experimental animal. From all the existing strategies, the promising strategy is live attenuated vaccines using recombinant inter-flavivirus.Key words: Dengue fever, Dengue virus, VaccineÂ AbstrakPenyakit demam berdarah merupakan penyakit endemis di Indonesia. Penyakit ini disebabkan oleh virus dengue yang terdiri dari serotipe DENV1, DENV2, DENV3, dan DENV4. Salah satu cara yang diharapkan dapat mengendalikan penyakit dengue adalah penemuan vaksin. Kajian makalah ini berdasarkan studi literatur. Hasil kajian menunjukkan beberapa strategi pengembangan vaksin untuk dengue saat ini adalah vaksin hidup dilemahkan (live attenuated vaccine), vaksin subunit, dan vaksin DNA. Strategi pengembangan vaksin masih menghadapi tantangan terutama formulasi vaksin yang dapat memicu respon imun seimbang terhadap keempat serotipe dan belum adanya hewan coba yang cocok. Strategi yang paling menjanjikan adalah vaksin hidup dilemahkan menggunakan metode rekombinan antar-flavivirus.Kata kunci: Demam Berdarah, Virus Dengue, Vaksin